2016
DOI: 10.1186/s12913-016-1478-3
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care use in urban areas in two European countries: Predisposing, enabling and pregnancy-related determinants in Belgium and the Netherlands

Abstract: BackgroundExamining determinants of antenatal care (ANC) is important to stimulate equitable distribution of ANC across Europe. This study (1) compares ANC utilisation in Belgium and the Netherlands and (2) identifies predisposing, enabling and pregnancy-related determinants.MethodsSecondary data analysis is performed using data from Belgium, and the Netherlands. The content and timing of care during pregnancy (CTP) tool measured ANC use. Non-parametric tests and ordinal logistic regression are performed to ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
14
1
Order By: Relevance
“…CoC indices in this study were also found to be different from those reported elsewhere. Low levels of CoC have been reported among antenatal women, with a lower proportion having a CoC score above 50%: 24% of antenatal women in Brussels 16 ; 26% in Brussels; and 30% in the Netherlands 17 . Meur et al 18 also reported a CoC score of 43% among pregnant women in France and CoC levels in the range of 28%–36% among health insurance beneficiaries in Taiwan 19 .…”
Section: Discussionmentioning
confidence: 99%
“…CoC indices in this study were also found to be different from those reported elsewhere. Low levels of CoC have been reported among antenatal women, with a lower proportion having a CoC score above 50%: 24% of antenatal women in Brussels 16 ; 26% in Brussels; and 30% in the Netherlands 17 . Meur et al 18 also reported a CoC score of 43% among pregnant women in France and CoC levels in the range of 28%–36% among health insurance beneficiaries in Taiwan 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that late onset initiation of ANC may be more important than the frequency of visits on influencing outcomes (3,6,9,10). Earlier work has reported that women with late ANC initiation are usually younger, higher parity or gravidity, without a partner, lower socioeconomic status, less educated, and have lower access to health services (5,11,12). Women who have unplanned pregnancies, recognize their pregnancy late, and had no complications in previous pregnancies will also tend to initiate ANC at later stages of their pregnancy (12).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work has reported that women with late ANC initiation are usually younger, higher parity or gravidity, without a partner, lower socioeconomic status, less educated, and have lower access to health services (5,11,12). Women who have unplanned pregnancies, recognize their pregnancy late, and had no complications in previous pregnancies will also tend to initiate ANC at later stages of their pregnancy (12). Moreover, women will not attend ANC if the quality of services is perceived as poor or their previous experiences were negative (13).…”
Section: Introductionmentioning
confidence: 99%
“…A similar finding was seen in a study conducted in Belgium and the Netherlands (41%). [ 14 ] Women who are over 35 years and above are more likely to use the ANC services than other age groups; however, studies in Tanzania and Myanmar reported that women of younger age group 15–24 years used ANC services more than other age groups. [ 15 16 ] In this study, about 58% women ≥35 years of age have experienced IPV whereas the prevalence rate in Brazil was 45.2%, 54.5% in Iran, 49% in Sri Lanka and 43.4% in Portugal.…”
Section: Discussionmentioning
confidence: 99%